Research on mapping recognition of arc welding molten pool characterisation and penetration state based on embedded system - Yanjun Zhu; Zhisheng Wu; Cuirong Liu (IET Computers & Digital Techniques)
Abstract In order to explore the mapping recognition of arc welding molten pool characterisation and penetration state, according to the idea of embedded system construction, this article adopts the idea of software and hardware co‐design to find the zero‐crossing point of the second derivative in welding image edge detection, and give a threshold. When the absolute value of the first‐order derivative exceeds the threshold and has a different sign with the first‐order derivative of the previous edge, it is judged as a valid edge. The welding current adopts a symmetrical pulsed AC square wave, and the proportion of heat flow input is high. At the base current, the arc light is darker, so a clear image is obtained. This article designs a simulation experiment to verify the effect of the embedded system in this article. From the experimental research, it can be known that the embedded system constructed in this article can play a certain role in the mapping recognition of the arc welding molten pool characterisation and penetration state.